Determinants Of Digital Literature And Learning Style On Critical Thinking Ability Of Students Of SMAN 1 Tukdana - Rochmatika, Indri; Yana, Enceng (Perspektif Pendidikan dan Keguruan, 2022)
This study aims to determine the effect of digital literacy and learning styles on students' critical thinking skills in economics lessons. This research is a descriptive quantitative research. The population in this study is the X grade students of SMA Negeri 1 Tukdana, Indramayu Regency in 2022 as many as 150 students. The selected sample was 71 students as respondents, then students were selected using random sampling technique. Data collection techniques were carried out using a questionnaire/questionnaire and documentation. The data analysis technique was carried out through the stages of research data description, classical assumption test, multiple linear regression test, and hypothesis testing. The results showed that; (1) digital literacy has a positive effect on critical thinking skills of SMA Negeri 1 Tukdana students, (2) learning styles of SMA Negeri 1 Tukdana students have a positive effect on critical thinking skills of SMA Negeri 1 Tukdana students, and (3) digital literacy and learning styles have a positive but not significant effect simultaneously on the critical thinking skills of class X students of SMA Negeri 1 Tukdana, Indramayu Regency.